The associations between self-reported anxiety symptoms and physical activity among university students in Finland - Marttinen, Eerik (2024)
In this thesis, I investigate the relationship between anxiety symptoms and physical activity among university students studying at Finnish universities. As anxiety is an increasing problem among students and exercise has been shown to alleviate anxiety, my aim is to determine whether there is a statistically significant association between anxiety and exercise among university students. My aim was to determine whether the amount of physical activity is related to the amount of anxiety, whether it makes a difference whether a person engages in physical activity in an organized environment or not, or whether it makes a difference whether a person engages in physical activity as an individual or in a group setting. My hypotheses were that the amount of physical activity would be negatively correlated with the amount of anxiety, and that the people who exercise in an organized environment or in a group setting would report lower levels of anxiety symptoms.